Optimalisasi Sistem Pentanahan Untuk Mengurangi Back Flashover Akibat Sambaran Petir Pada Tower Sutt Penghantar Sentul Cibinong - Tun Sri Rajunul Muha; Yusreni Warmi; Zulkarnaini; Arfita Yuana Dewi; Erhaneli (CV. Creative Tugu Pena, 2024)
This study aims to analyze the impact of grounding system improvements on crossarm voltage and the potential occurrence of back flashover in power transmission networks. Initially, the grounding resistance reached 33.2 Ω, exceeding the IEEE Std 80-2000 standard, with lightning current assumed between 20 kA and 80 kA. Simulation results show that crossarm voltage without considering the corona effect reached 1493.715 kV, while with the corona effect, it reached 1533.7 kV, both exceeding the flashover voltage threshold of 1440.439 kV. After improvements were made by extending the grounding electrode, the resistance decreased to 7.489 Ω (simulated) and 5.20 Ω (measured in the field). The crossarm voltage without corona effect dropped to 1438.829 kV and 1433.947 kV, approaching or below the flashover voltage limit. However, crossarm voltage with the corona effect remained above the threshold at 1508.4 kV and 1505.9 kV. These results indicate that while grounding improvements effectively reduce back flashover risk, the corona effect remains a factor that must be further mitigated to achieve optimal protection. Gateway have a positive and significant influence on SMEs' performance.